Zombie as Victim in Film, TV Series, and Video Games - Bubnowska, Marta (Zagadnienia Rodzajów Literackich, 2025)
The visual culture of the 21st century has reimagined the zombie. The zombie figure has started appearing in every corner of contemporary pop culture, particularly over the last two decades, captivating audiences with outbreak narratives on screens. The main point of my research is to elucidate how and why the zombie figure has transformed from a mindless, slowly-strolling monster in Night of the Living Dead (1968) by George A. Romero to fast, re-introduced apocalyptic zombies in the newest Resident Evil (2023) or to the excluded, outcasted monster in TV Shows such as as iZombie (2015) or In the Flash (2013–2014). My goal is to demonstrate that the figure of a zombie aligns with the concepts of “the Other” and “the Abject,” depicting monsters that are victims of human oppression, rather than perpetrators. On the literary level, the zombie apocalypse exposes a range of societal fears and traumas, not only related to death or epidemiological threats, but also fears associated with the economy, including corporate realms, capitalistic structures, economic crises, and political and social systems. They challenge the boundaries of submission and resistance, as well as those of race, sex, nation, and national identity. Following that, I aim to answer what a zombie is in modern texts, why we are afraid of it, and what we are so scared of outside the screen.